Analisis Perbandingan Daya Dukung Pondasi Tiang Pancang Menggunakan Metode Luciano De Court dan Plaxis Dengan Pile Driving Analyzer (PDA) Test Pada Pembangunan Gedung Research Center UPN Veteran Jawa Timur - Philipus Bagus Putra Arliyanto Arliyanto; Muhammad Shofwan Donny Cahyono; Yoanita Eka Rahayu Yoanita Eka Rahayu (Ge-STRAM: Jurnal Perencanaan dan Rekayasa Sipil, 2024)
Pile foundations are classified into deep foundation structures which are used in the construction of multi-storey buildings where the application requires a depth of more than 4 meters in order to withstand the magnitude of the existing load. The purpose of this study is intended to test the bearing capacity and settlement in the construction of the Research Center Building at the Surabaya Veterans National Development University by applying the related calculation method, of course, must be based on the data obtained, namely the Standar Penetration Test (SPT) and the conditions of the soil contour of the project under review where the soil contour of the project is cohesive. In this study, the analysis of the bearing capacity using the Luciano De Court – Quaresma (1982) method and the Plaxis software. Furthermore, for the analysis of settlement using the Vesic method (1997) and Plaxis software. As for the Pile Driving Analyzer (PDA) Test data, it is used as a comparison between related methods. The results of the calculation of the bearing capacity ultimate between the Luciano De Court method and Plaxis and the results of the Pile Driving Analyzer (PDA) Test for a 500 mm pile at point 161 and point 261 respectively are 189 tons and 279 tons for the Pile Driving Analyzer (PDA) Test, 281 tons for the analysis of the Luciano De Court Method and 300 tons for the analysis of the Plaxis program assistance. Furthermore, the settlement values for the 500 mm pile at point 161 and point 261 respectively are 27,19 mm and 23,06 mm for the Pile Driving Analyzer (PDA) Test, 23 mm in the analysis of the Luciano De Court method and 20,17 mm in the analysis using Plaxis software.